1996
DOI: 10.1152/ajpcell.1996.271.3.c929
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatases independently regulate vesicle movement and microtubule subpopulations in hepatocytes

Abstract: To investigate the regulation of microtubule (MT)-based vesicle transport and the interphase MT array in hepatocytes, we have used okadaic acid (OKA) and microcystin (MCYST), two toxins that inhibit serine-threonine protein phosphatases (PP) 1 and 2A, to alter cellular phosphorylation. Video-enhanced differential interference contrast microscopy analysis revealed that both toxins inhibited the frequency, velocity, and run length of MT-dependent vesicle movements dose dependently between 50 and 500 nM. At our m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 24 publications
3
46
1
Order By: Relevance
“…In intact hepatocytes exposed to PP inhibitors, we have shown that MT-dependent vesicle movements are significantly impeded [9]. These changes are not associated with any common changes in the MT array ( Figure 3) [9].…”
Section: Dynein Phosphorylation Is Associated With Reduced Atpase Actmentioning
confidence: 83%
See 4 more Smart Citations
“…In intact hepatocytes exposed to PP inhibitors, we have shown that MT-dependent vesicle movements are significantly impeded [9]. These changes are not associated with any common changes in the MT array ( Figure 3) [9].…”
Section: Dynein Phosphorylation Is Associated With Reduced Atpase Actmentioning
confidence: 83%
“…Previous work has shown that 500 nM MCY or 250 nM OKA results in comparable reductions in MT-based vesicle movements and receptor-mediated endocytosis [9,10]. As shown in Figure 1, the phosphorylation of several components of the cytoplasmic Figure 1 Cytoplasmic dynein-associated polypeptides phosphorylated in hepatocytes exposed to OKA or MCY Hepatocytes were labelled with 32 P[P i ] (0.3 mCi /1.5i10 6 cells, 2 h) prior to treatment with PP inhibitors (250 nM OKA or 500 nM MCY, 60 min), and lysates were exposed to UV light in the absence (no UV-VAN) or presence (UV-VAN) of 100 mM VAN and 2 mM MgATP.…”
Section: Inhibition Of Pps Causes Increased Phosphorylation Of the Dymentioning
confidence: 94%
See 3 more Smart Citations